The history of music - Biddison, Clare (My University, 1907)
Introduction: Fortunately history has something to record beside bloodshed and wrong. It is well that the song of the morning stars and the heavenly chant of "Peace on earth and good will to men", have been preserved as well as the stories of assassination, adultery, and massacre, and if there is reason why we should burrow into the past to learn the lessons of government, which is the method by which "One man ruleth over another unto his own hurt," so is there reason why we should delve into the past and consider the origin and progress of that divine art which has soothed the savage breast and has inspired man to noble deeds, comforted humanity in the depths of sorrow, lightened the laborer's toil and drawn man most powerfully heavenward. The origin of music is older than the "Art preservative". Whether ape-like men imitated with the voice the song of the birds, the roar of the thunder, the dripping of the waters, the breaxing of the waves and the whistling of the winds through the forest,or whether a God-born Adam waking with the dawn broke forth in irresistable praise of the Creator is perhaps debatable, but as far back as go any of the ancient writings, whether on parchment or on the rocks, there are evidences that man found beauty in sound as well as in sight and that the most ancient peoples voiced the glories of their histories, that the most ancient lovers sang of their loved ones, and that even savage mothers crooned the folk-lore.to their babes.
Citation: Biddison, Clare. The history of music. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Music; History of Music; Music Theory; Theses